Bathsheba survives - Koenig, Sara M. (Columbia, SC : University of South Carolina Press, 2018)
A portrait of Bathsheba, a biblical woman seen through the centuries as everything from adviser to temptress to victim.
Why Bathsheba? -- Bathsheba in the Bible: identifying gaps -- Bathsheba revealed in rabbinic literature -- Bathsheba as type and trope in the patristic -- Bathsheba in the bath in the medieval period -- Bathsheba reformed in the Reformation -- Bathsheba enlightened in the enlightenment -- Bathsheba told, sung, acted, and politicized in the contemporary world -- Bathsheba unfinalized.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
Master record variable field(s) change: 072
Keywords: Bathsheba -- (Biblical figure); Bathsheba -- (Biblical figure); RELIGION / Biblical Studies / Old Testament; RELIGION / Biblical Biography / Old Testament; Electronic books